2012
DOI: 10.3390/rs4092818
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Forest α-Diversity and Floristic Composition — On the Added Value of LiDAR plus Hyperspectral Remote Sensing

Abstract: The decline of biodiversity is one of the major current global issues. Still, there is a widespread lack of information about the spatial distribution of individual species and biodiversity as a whole. Remote sensing techniques are increasingly used for biodiversity monitoring and especially the combination of LiDAR and hyperspectral data is expected to deliver valuable information. In this study spatial patterns of vascular plant community composition and α-diversity of a temperate montane forest in Germany w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 86 publications
(108 reference statements)
1
71
0
1
Order By: Relevance
“…Satellite-derived time-series of the Enhanced Vegetation Index were used to quantify functional diversity at the ecosystem level through the identification of Ecosystem Functional Types, defined here as ecological entities that have similar properties and dynamics of primary production. Numerous studies have successfully evaluated the use of remotely-sensed spectral diversity to estimate species richness [79][80][81][82][83] and species beta-diversity [84,85]. Our study focused not on estimating the diversity of species composition or turn-over, but on assessing the diversity of ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite-derived time-series of the Enhanced Vegetation Index were used to quantify functional diversity at the ecosystem level through the identification of Ecosystem Functional Types, defined here as ecological entities that have similar properties and dynamics of primary production. Numerous studies have successfully evaluated the use of remotely-sensed spectral diversity to estimate species richness [79][80][81][82][83] and species beta-diversity [84,85]. Our study focused not on estimating the diversity of species composition or turn-over, but on assessing the diversity of ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Over complex terrain areas, the inclusion of high-resolution topographical and structural variables derived from a LiDAR point cloud may represent a relevant contribution to the estimation of diversity, as demonstrated in several studies [20,41,46,47] including this one. Because of the singular conditions of the complex native forest of the Andes foothills of central Chile, it is expected that more robust results will be obtained by modeling plant diversity using the differentiation of different plant strata (tree, shrub, and herb canopies separately), due to the high capacity of LiDAR to capture the variability of these strata, as shown in other studies [26,57].…”
Section: Ecological Implicationsmentioning
confidence: 95%
“…The results of this research did not allow us to confirm the spectral variation hypothesis on a local scale, even though Oldeland et al [56] suggested that the use of hyperspectral information should improve monitoring of species diversity. In this light, recent studies [43,44] have proven that the hyperspectral information from airborne sensors can significantly enhance the predictive power of models not only because of the spectral information but also because of the improvement provided by the spatial resolution [24,26,41,58,59]. Another relevant source of information could be an analysis of seasonal and annual variability that can provide an additional element in estimating biodiversity [24], particularly in deciduous forests like Monte Oscuro.…”
Section: Ecological Implicationsmentioning
confidence: 99%
See 2 more Smart Citations